Improving maternal nutrition in India through integrated hot-cooked meal programs: A review of implementation evidence - Kachwaha, Shivani; Avula, Rasmi; Menon, Purnima; Sethi, Vani; Joe, William; Laxmaiah, Avula (International Food Policy Research Institute, 2021)
A notable approach to addressing maternal undernutrition during pregnancy in India in recent years has been the integration of hot-cooked meals (HCM) for pregnant and lactating women together with the provision of other health/nutrition services. Called the One Full Meal (OFM) program, these efforts aim to improve maternal nutrition and health across India by bundling center-based HCM with other nutrition services and behavior change communication implemented through the Integrated Child Development Services (ICDS) scheme. The program is offered at anganwadi centers (AWCs) and has been implemented in eight states in India, including Andhra Pradesh, Chhattisgarh, Gujarat, Karnataka, Maharashtra, Telangana, Madhya Pradesh, and Uttar Pradesh. Although the OFM program has been implemented since 2013, there is limited consolidated insight on its effectiveness or on broader lessons for implementation. The objectives of this evidence review of the OFM program are, therefore, to (1) compare the different state OFM program models on their objectives, implementation elements, cost norms and monitoring mechanisms; (2) develop program impact pathways on the potential ways in which the program could influence intended outcomes; and (3) examine the availability of evidence underpinning the program’s intended pathways to impact.